A Nested Eight-Channel Transmit Array With Open-Face Concept for Human Brain Imaging at 7 Tesla - Williams, Sydney N.; Allwood-Spiers, Sarah; McElhinney, Paul; Paterson, Gavin; Herrler, Jürgen; Liebig, Patrick; Nagel, Armin M.; Foster, John E.; Porter, David A.; Gunamony, Shajan (Frontiers in Physics, 2021)
Purpose: Parallel transmit technology for MRI at 7 tesla will significantly benefit from high performance transmit arrays that offer high transmit efficiency and low mutual coupling between the individual array elements. A novel dual-mode transmit array with nested array elements has been developed to support imaging the human brain in both the single-channel (sTx) and parallel-transmit (pTx) excitation modes of a 7 tesla MRI scanner. In this work, the design, implementation, validation, specific absorption rate (SAR) management, and performance of the head coil is presented. Methods: The transmit array consisted of a nested arrangement to improve decoupling between the second-neighboring elements. Two large cut-outs were introduced in the RF shield for an open-face design to reduce claustrophobia and to allow patient monitoring. A hardware interface allows the coil to be used in both the sTx and pTx modes. SAR monitoring is done with virtual observation points (VOP) derived from human body models. The transmit efficiency and coverage is compared with the commercial single-channel and parallel-transmit head coils. Results: Decoupling inductors between the second-neighboring coil elements reduced the coupling to less than -20dB. Local SAR estimates from the electromagnetic (EM) simulations were always less than the EM-based VOPs, which in turn were always less than scanner predictions and measurements for static and dynamic pTx waveforms. In sTx mode, we demonstrate improved coverage of the brain compared to the commercial sTx coil. The transmit efficiency is within 10% of the commercial pTx despite the two large cut-outs in the RF shield. In pTx mode, improved signal homogeneity was shown when the Universal Pulse was used for acquisition in vivo. Conclusion: A novel head coil which includes a nested eight-channel transmit array has been presented. The large cut-outs improve patient monitoring and reduces claustrophobia. For pTx mode, the EM simulation and VOP-based SAR management provided us with greater flexibility to apply pTx methods without the limitations of SAR constraints. For scanning in vivo, the coil was shown to provide an improved coverage in sTx mode compared to a standard commercial head coil.